Report of the Survey of Small Scale and Cottage Industries in Baroda Dist. - V. Y. Kolhatkar (Planning Commission Government of India, 1972)
The survey report on small scale and cottage industries in Baroda District (1953–1959) provides a detailed analysis of the Calico printing and lacquer woodwork industries. The study highlights declining calico printing units in Padra and Baroda due to mechanized competition, while lacquer woodwork in Sankheda shows modest growth. The report examines production processes, economic viability, raw material constraints, labor challenges, and market dynamics, including sales trends and profit margins. It emphasizes the precarious livelihoods of artisans and the cultural significance of traditional products like Ghodia cradles. Recommendations include training programs, cooperative models for bulk material procurement, marketing support, and government interventions to modernize techniques and enhance competitiveness. The study underscores the urgent need for strategic measures to ensure the sustainability and growth of these heritage industries.
Planning Commission Research Programmes Committee
Keywords: Small Scale Industries; Cottage Industries; Baroda District; Calico Printing; Lacquer Wood Work; Artisans; Traditional Crafts; Sankheda; Ghodia; Production Costs; Market Challenges; Cooperative Model